Bone Subtraction Iodine Imaging Using Area Detector CT for Evaluation of Skull Base Invasion by Nasopharyngeal Carcinoma - Hiyama, T.; Kuno, H.; Sekiya, K.; Tsushima, S.; Sakai, O.; Kusumoto, M.; Kobayashi, T. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Conventional CT has generally lower detectability of bone marrow invasion than MR imaging due to lower tissue contrast. The purpose of this study was to compare the diagnostic performance of conventional CT alone or in combination with bone subtraction iodine imaging using area detector CT for the evaluation of skull base invasion in patients with nasopharyngeal carcinoma.MATERIALS AND METHODS: Forty-four consecutive patients who underwent contrast-enhanced CT using 320–row area detector CT and contrast-enhanced MR imaging for nasopharyngeal carcinoma staging between April 2012 and November 2017 were enrolled in this retrospective study. Bone subtraction iodine images were generated by subtracting pre- and postcontrast volume scans using a high-resolution deformable registration algorithm. Two blinded observers evaluated skull base invasion at multiple sites (sphenoid body, clivus, bilateral base of the pterygoid process, and petrous bone) using conventional CT images alone or in combination with bone subtraction iodine images. Examination of MR and CT images by an experienced neuroradiologist was the reference standard for evaluating sensitivity, specificity, and area under the receiver operating characteristic curve.RESULTS: Twenty-six patients (59%) showed skull base invasion at 84 sites on the reference standard. Conventional CT plus bone subtraction iodine images showed higher sensitivity (92.9% versus 78.6%, P = .02) and specificity (95.6% versus 86.1%, P = .01) than conventional CT images alone for evaluating skull base invasion. The area under the receiver operating characteristic curve for conventional CT plus bone subtraction iodine (0.98) was significantly larger (P < .001) than the area under the receiver operating characteristic curve for conventional CT alone (0.90).CONCLUSIONS: Conventional CT plus bone subtraction iodine performs more closely to the accuracy of combining CT and MR imaging compared with conventional CT alone.AUCarea under the receiver operating characteristic curveBSIbone subtraction iodineCCTconventional CTNPCnasopharyngeal carcinoma